The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20959/wjpps20175-9143
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid: A Pharmacologically Significant Scaffold

Abstract: Flavonoids belong to a group of polyphenolic compounds, which are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Statistical analysis indicated that TPC and TFC of EE were significantly higher ( p < 0.01) than that of WE. Plant polyphenols and flavonoids have been widely used in various medicines and food products due to their wide range of pharmacological activities, such as antioxidants, antimicrobial, anticancer, anti-inflammatory, hepatoprotective, antiviral, antiatherosclerotic, antispasmodic, and enzyme inhibitory activities ( Fraga, 2010 ; Agrawal, 2011 ; Murti and Sharma, 2017 ). The H. flavum rhizome WE and EE exhibited high TPC and TFC values, which can be used as a rich source of phenolics and flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis indicated that TPC and TFC of EE were significantly higher ( p < 0.01) than that of WE. Plant polyphenols and flavonoids have been widely used in various medicines and food products due to their wide range of pharmacological activities, such as antioxidants, antimicrobial, anticancer, anti-inflammatory, hepatoprotective, antiviral, antiatherosclerotic, antispasmodic, and enzyme inhibitory activities ( Fraga, 2010 ; Agrawal, 2011 ; Murti and Sharma, 2017 ). The H. flavum rhizome WE and EE exhibited high TPC and TFC values, which can be used as a rich source of phenolics and flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…comprises polysaccharides (mucilaginous), condensed tannins, flavonoids, quercetin glycosides (rutin, quercitrin, and isoquercitrin), kaempferol glycosides and phenolic acids (caffeic, p-coumaric, and chlorogenic acids) [38]. Flavanoid content of Tilia cordata (hyperoside, tiliroside) has several pharmacological activities, such as antifungal, antiviral, anti-inflammatory and antioxidant activities [39]. Although Tilia cordata has not been evaluated clinically for symptomatic relief of flu symptoms, this medicinal plant may be beneficial in relieving respiratory symptoms due to its anti-inflammatory activity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological investigations showed that A. officinalis possess anti-complement, anti-inflammatory, antitussive, antioxidant and hypoglycemic effects while T. cordata possess anti-fungal, anti-viral, anti-inflammatory and Antioxidant activities. 16,23 Gutiérrez et al, 21 and Anand et al, 24 reported that P. guaja are effective as antioxidant, hepatoprotection, anti-allergy, antimicrobial, antigenotoxic, antiplasmodial, cytotoxic, antispasmodic, cardioactive, anticough, antidiabetic, antiinflamatory and antinociceptive agent. Therefore, this study was designed to examine the inhibitory effect of the flowers from A. officinalis, leaves from T. cordata and P. guaja individually as well as in combination as a formula against pathogens that caused respiratory infections.…”
Section: Introductionmentioning
confidence: 99%